Motivational component of a teacher’s psychological and pedagogical potential: from theory to practice - M. A. Romanova; V. N. Punchik; N. S. Murodkhodzhaeva (Кардиоваскулярная терапия и профилактика, 2024)
Aim. To determine the motivational component of the teacher’s psychological and pedagogical potential, as well as the differences between potential and real psychological profile and professional activity of the individual.Material and methods. To study motivation, a questionnaire was used. In addition to the quantitative data necessary for the evidence base, qualitative processing was carried out — each answer was considered separately. The quantification analysis of social motives at the stage of diagnosis and development of their psychological and pedagogical potential served as the basis for discussing the results.Results. The results show that before the start of the experiment, the mean values of the motive for helping people in the experimental and control groups of subjects were almost the same. After the end, the strength of this motive increased in both groups. However, in the control group the differences before and after the experiment were insignificant. In the experimental group there were more noticeable significant changes: t=2,10; p≲0,05. This means that the development of psychological and pedagogical potential among students who will become primary school teachers in the future had a positive effect on the strength of their motive for helping people. The positive results are justified by certain work that the teachers carried out with the experimental group subjects according to the program compiled by the author. The results were especially influenced by the fact that group forms of work were used during the experiment. In addition, work was carried out with students aimed at developing their affiliation motive, which is positively related to the motive of helping people. Strengthening the motive may also be associated with the acquisition of positive experiences in teaching and raising children during teaching practice, which contributes to motivation to help others.Conclusion. The developed model of the psychological and pedagogical potential of the future primary school teacher includes structural components and areas of development. Capacity building is successful with timely diagnosis of development levels and changes in the education content. The developed diagnostic practice and capacity building concept are effective.